From housing to human settlements: the role of public space in integrated housing developments - McGarry, Michelle Samantha (Urban Management, 2018)
Since 1994 the post-apartheid South African Government has recognized the importance of housing in improving the quality of life of its citizens. Following 10 years of a housing delivery model that saw the provision of nearly 1.6 million houses, the National Government introduced a new policy that sought to shift away from an emphasis on housing and rather a holistic focus on the quality of the settlement established. This new policy, Breaking New Ground (BNG) promoted the establishment of well-managed, liveable and equitable settlements incorporating social and economic infrastructure. The quality of the urban environment and the quality of public spaces within urban developments has been identified as contributing towards improving quality of life within these settlements. In mixedincome, integrated settlements - like those BNG claims to produce - the importance of public space is further emphasised because it compensates for limited space of the private home. However, these spaces are often considered as "nice-to-haves" and neglected in favour of basic services or housing. Despite the importance of public space and its contribution to the creation of sustainable human settlements, these spaces, although planned for in the initial phases of a development, still remain largely undeveloped. This research therefore questions whether public spaces within integrated housing developments are being used as intended. It also questions to what extent the necessity for increased urban densification has affected the provision of public space in integrated housing developments. This research attempts to answer the question from the perspective of professionals involved in the planning and implementation of integrated housing developments and not from the perspective of residents. A qualitative research approach has been adopted. Three settlements each representing an integrated housing development implemented in line with BNG principles and incorporating public spaces were selected as case studies and in-depth interviews with professionals involved in the planning and implementation of these developments were conducted. The research found that while public spaces are considered as beneficial and are included in the planning stages of a development, in reality the lived experience often differs. While the objectives of housing policies are to create sustainable human settlements, professionals still struggle to translate these objectives into practical guidelines and standards. Finally, it was observed that while public spaces do play a role in the shift from housing to human settlements, the process is one that occurs incrementally and over a period of time.